Characterization and Classification of Soils under Various Land Use Types in Dalisodo Village, Wagir Sub-District, Malang Regency - Retno Wilujeng; Widowati Widowati (Acta Solum, 2025)
This study aims to examine the physical and chemical properties of soil, morphology, and soil classification in Dalisodo Village, Wagir District, Malang Regency, and their implications for land management. Observations were conducted at three locations representing different land-use types: Napier grass monoculture, coffee agroforestry, and open grass. Soil morphology was described in the field, while physical and chemical analyses were conducted using standard laboratory methods. The results indicate that the soil is predominantly clay-textured, with a granular to subangular blocky structure, an acidic pH, and a very low to moderate organic carbon content. N, P, and K levels vary from low to moderate, CEC ranges from moderate to high, and base saturation ranges from low to very high. Soil classification reveals a dominance of Inceptisols and Vertisols in Udic soil moisture regimes, with soil profiles characterized by Typic Hapluderts (Point 1), Dystric Eutrudepts (Point 2), and Chromic Hapluderts (Point 3). These findings provide important information for land management, as vertisols require attention to drainage, water retention, and liming to optimize productivity. Inceptisols require organic amendments and soil fertility management to support sustainable agricultural or agroforestry systems. Emphasis on soil classification helps determine appropriate land management strategies, improves fertilizer efficiency, and supports the sustainability of the region’s agricultural ecosystem.